Synthesis and Antimicrobial Activity of 1-(9'-Acridinyl)-5-(4-Substituted Phenyl) Tetrazoles - P. Kavitha, Helen (Asian Journal of Chemistry, 2016)
This paper reports the synthesis and antimicrobial activity of some 1-(9'-acridinyl)-5-(4-substituted phenyl) tetrazoles.